PENATALAKSANAAN HIPERTENSI PADA LANJUT USIA - Kuswardhani, RA Tuty (journal of internal medicine; Vol. 7, No. 2 Mei 2006, 2012)
The more increasing of life expectancy is more complex disease in elderly. One of cause disease in elderly is hypertension The isolated systolic hypertension (ISH) the most risk factor in stroke, coronary failure, and coronary heart disease, their role is predicted more their in the youth. The definition of hypertension is not change in the age : systolic blood pressure (SBP) 140 mmHg, and or diastolic blood pressure (DBP) 90 mmHg. The Joint National Committee on Prevention, Detection, Evaluation and Treatment of high blood pressure (JNC VI) and WHO or International society of hypertension guidelines sub committees agree that SBP and DBP, both are used to classify the hypertension. Patophysiology of blood pressure is not clear. The most effect of the mortal aging in the cardio vascular system includes the changing of compliance aorta and systemic vessels. The thickening of aorta wall are major vessels are increasing while the elasticity of vessel is decreasing in aging. This changing brings the compliance of aorta is decreasing and the major vessel, it causes the increasing of peripheral vascular resistance. Baroreceptor sensitivity is also changing in aging. The changing in the metabolism of baroreceptor reflex possibly can explain the existence the variability pressure. The changing of vasodilatation adrenergic and vasoconstriction of adrenergic a in balance will tend vasoconstriction are will bring the increasing of peripheral vessel resistance and blood pressure. The management of hypertension in the elderly includes behavior, exercise, and pharmacology therapy.
Keywords: hypertension, management, elderly PENDAHULUAN